f ( x ) is a polynomial function which satisfies the following condition: f ( x ) + f ( x 1 ) = f ( x ) f ( x 1 ) . If f ( 7 ) = 2 4 0 2 , what is the value of f ( 1 1 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great job! Your solution is very meticulous.
[This is an almost complete solution. Looking over Sandor's solution, it is equivalent to his, so you can view the details there.]
Let g ( x ) = f ( x ) − 1 . We have
1 = f ( x ) f ( x 1 ) − f ( x ) − f ( x 1 ) + 1 = [ f ( x ) − 1 ] [ f ( x 1 ) − 1 ] = g ( x ) g ( x 1 ) .
Claim: The only polynomial that satisfies this condition is g ( x ) = ± x n .
Proof: Let
g
(
x
)
=
∑
i
=
0
n
a
i
x
i
with
a
n
=
0
.
We have
(
∑
a
i
x
i
)
×
(
∑
a
i
x
−
i
)
=
1
×
x
0
.
Compare the coefficients
x
n
,
x
n
−
1
,
…
,
x
0
.
Conclude that
a
0
,
a
1
,
a
2
,
…
,
a
n
−
1
=
0
and
a
n
=
±
1
.
Any example of a non-polynomial function that fits f ( x ) f ( 1 / x ) = 1 for all x ∈ R − { 0 } ?
Log in to reply
Lots. Uncountably many in fact. Think about it.
Hint: What is f ( π ) ?
I got this by intuition. I put x=1. Found that f(1)=2. Then I found that 2402=7^4+1. I saw that worked for f(1) as well. So, I just deduced f(x)=x^4+1
By inspection, we can see the following type of polynomial functions satisfy the given condition. f ( x ) = 1 + x k Now, f ( 7 ) = 1 + 7 k ⟹ 7 k = 2 4 0 1 ⟹ k = 4 Therefore, f ( 1 1 ) = 1 1 4 + 1 = 1 4 6 4 2
[P.S. I'm not sure about the uniqueness of this solution. If you find other functions that work as well, please let me know.]
We note that if α is a zero of f ( x ) then so is α 1 . Therefore f ( x ) is a reciprocal polynomial (A polynomial is called reciprocal if a i = a n − i where a i are coefficients of the polynomial and n is the degree.) whose degree is 2 n as it should have even number of terms. Now every reciprocal polynomial can be written as f ( x ) = x n g ( x + x 1 ) , putting this in the given relation and after reducing it we get g ( x + x 1 ) { g ( x + x 1 ) − x n − x n 1 } = 0 . Since f ( 7 ) = 2 4 0 2 , hence g ( x + x 1 ) = x n + x n 1 . Therefore f ( x ) = x 2 n + 1 , and using f ( 7 ) = 2 4 0 2 we get f ( x ) = x 4 + 1 . Thus f ( 1 1 ) = 1 4 6 4 2 .
Problem Loading...
Note Loading...
Set Loading...
Let f ( x ) = i = 0 ∑ n a i x i where a n = 0 . In this form the condition above looks like i = 0 ∑ n a i x i + i = 0 ∑ n a i x − i = ( i = 0 ∑ n a i x i ) ⋅ ( i = 0 ∑ n a i x − i ) .
Clearly f is not a constant function, otherwise we would have f ( x ) = f ( 7 ) = 2 4 0 2 and 2 ⋅ 2 4 0 2 = 2 4 0 2 2 from the condition, which is a contradiction. This means that n ≥ 1 .
Observe that on the left side for every i ≥ 0 the coefficient of x i is a i . If we evaluate the product on the right side we can see that for an i ≥ 0 the exponent of x in the result will be i if and only if we multiply together the terms in the form a k + i x k + i and a k x − k for 0 ≤ k ≤ n − i . Thus for every i ≥ 0 the coefficient of x i will be k = 0 ∑ n − i a k + i a k . Two polynomials are equal if and only if all the respective coefficients are equal, hence we obtain a i = k = 0 ∑ n − i a k + i a k for every 0 ≤ i ≤ n . (1)
Considering the last equation with i = n we get a n = a n a 0 , which implies a 0 = 1 . Next we are going to show by induction that a i = 0 for every 0 < i < n . Using equation (1) for i = n − 1 we obtain a n − 1 = a n a 1 + a n − 1 a 0 . From a 0 = 1 we can deduce that a n a 1 = 0 hence a 1 = 0 since a n = 0 . Assume by induction that our claim is true for every 0 < i < j . Then applying (1) to n − j leads us to a n − j = k = 0 ∑ j a k + n − j a k where our induction hypothesis yields the terms for 0 < k < j to be 0, so the equation can be simplified into the form a n − j = a n a j + a n − j which implies a j = 0 in view of a n = 0 . Henceforth our induction is complete.
We have shown that a 0 = 1 and a i = 0 for 0 < i < n so our function is in the form a n x n + 1 . Then from the original condition we obtain a n x n + 1 + a n x − n + 1 = ( a n x n + 1 ) ( a n x − n + 1 ) ⇒ a n x n + a n x − n + 2 = a n 2 + a n x n + a n x − n + 1 ⇒ a n 2 = 1 ⇒ a n = ± 1
Hence f ( x ) = ± x n + 1 . Assuming f ( x ) = − x n + 1 we would get 2 4 0 2 = f ( 7 ) = − 7 n + 1 ≤ − 6 < 2 4 0 2 by n ≥ 1 so f ( x ) = x n + 1 . For x = 7 we have 7 n + 1 = f ( 7 ) = 2 0 4 2 which implies that n = 4 so f ( x ) = x 4 + 1 . Putting in x = 11 we obtain the final answer to be 14642.